1995
DOI: 10.1002/pen.760352206
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of liquid‐liquid mixing: A 2‐zone model

Abstract: The development of multiphase liquid-liquid morphologies during mixing at small Reynolds numbers has been modeled. The mixing process is divided into i) stretching of dispersed drops, ii) breakup of the liquid threads formed, and iii) coalescence of the final droplets upon collision. Rules and criteria of the distinct processes are presented and combined to a general 2-zone mixing model simplifying the flow field into a sequence of alternating "strong and weak zones." In a "strong zone," dispersed drops and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
110
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 31 publications
1
110
0
1
Order By: Relevance
“…Model I augments the ideas presented by Janssen and Meijer (1995). The basic idea is to divide the mixer into two types of zones, strong and weak.…”
Section: Outline Of This Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Model I augments the ideas presented by Janssen and Meijer (1995). The basic idea is to divide the mixer into two types of zones, strong and weak.…”
Section: Outline Of This Workmentioning
confidence: 99%
“…The time for the drop to break under ow is calculated from t break = t crit + t grow , where t crit is found using Eq. (4.2) and t grow is estimated by t grow = 1:4=˙ (Janssen & Meijer, 1995). If the drop is able to break in the time allowed, s ¿ t break , the drop is replaced by the corresponding distribution of drops produced upon breakup.…”
Section: Strong Zonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Grizzuti and Bifulco (1997), Vinckier et al (1998), and Minale et al (1997Minale et al ( , 1998 showed, by means of rheological experiments and optical microscopy (OM), that the steady-state morphology is reached only after a certain critical shearing time. However, Janssen and Meijer (1995) reported that flow conditions might exist in which more that one morphology is possible. For shear rates lower than the critical one, the dynamic equilibrium between breakup and coalescence cannot be obtained, or, at least, it cannot be reached in a reasonable shearing time.…”
Section: Introductionmentioning
confidence: 99%